Perancangan Sistem Kepuasan Masyarakat Terhadap Pelayanan Publik Dengan Metode Analytical Hierarchy Process (AHP) - Petrus Sokibi; Nurul Bahiyah (ITEJ (Information Technology Engineering Journals), 2018)
Talun sub-district is a government institution that provides public services to the public, which at this time there is no assessment of service satisfaction from the community so that the District Talun cannot know the assessment or complaints from the public to public services provided. The research aims to determine the level of public satisfaction of Public Service in Talun Sub-district. AHP is a complex multi-criteria decision-making method, in an unstructured situation into sections that are then shaped into functional hierarchies to present problems to be solved and then build a priority sequence for alternatives by pairwise alternative comparisons based on judgments of decision makers against a system. The appraisal application yields the value of the public satisfaction level and the eigenvector ranked according to the highest data as the final value of the AHP calculation so that the eigenvector value obtained can facilitate the Camat to see which elements of service are not good.